A Subclass of Harmonic Univalent Functions Defined by Salagean Integro Differential Operator - Hasan Bayram (Al-Qadisiyah Journal of Pure Science, 2020)
In this paper, we scrutinize some fundamental features of a subclass of harmonic functions defined by a new operator. Like coefficient inequalities, convex combinations, distortion bounds.